THE ROLE OF LEARNING THROUGH EXPERIMENTS IN SOCIETY (Modern education and development, 2025)
This article presents an analysis of the role of experimental learning in society, the importance of experiments in scientific, technological, social and medical fields. The widespread use of experiments in society and their importance in various fields are discussed, and experiments are used in scientific research to discover new knowledge and test existing theories.